Research on structure and technological parameters of multi-channel cold spraying nozzle - Hu, Wenjie; Tan, Kun; Markovych, Sergii; Cao, Tingting (Eastern-European Journal of Enterprise Technologies, 2021)
Cold spraying technology is a method to obtain coating by the high-speed collision of particles with the substrate through supersonic (300–1200 m/s) propulsion gas. The deposition process is mainly mechanical bonding, which has attracted more and more attention in engineering applications. The critical component of a cold spraying system is the nozzle. The performance of the nozzle directly affects the quality of the material surface coating. Therefore, the discussion of the nozzle is of great significance. At present, there are many examples of cold spraying single-channel nozzles in engineering, but there are few reports about multi-channel cold spraying nozzles. This paper explores and studies the multi-channel cold spraying nozzle, designs a special three internal channel nozzle, and adopts a 90° angle in the divergent section of the nozzle. When spraying in a small area, the nozzle with angle has apparent advantages for spraying more areas. The powder injection pressure, particle size, recovery coefficient, and internal channel position are analyzed, which affect the particle trajectory. Combined with these factors, the multi-channel nozzle is optimized and improved to solve the problem of particle collision with the inner wall of the nozzle. Finally, the technological parameters of aluminum, titanium, copper, nickel, magnesium, and zinc powders are preliminarily studied using the multi-channel nozzle. The results show that the multi-channel nozzle meets the critical velocity requirements of copper, magnesium, and zinc powder spraying in the homogeneous (powder and matrix are the same material) and aluminum powder spraying in the case of heterogeneous (powder and matrix are different materials), the multi-channel nozzle has a sound engineering application prospect and provides a specific reference for relevant technicians.